Analisis Faktor-Faktor Eksternal Yang Mempengaruhi Produktivitas Tenaga Kerja Pada Pekerjaan Pembuatan Batako - HENONG, Sebastianus Baki; LAKE, Reginaldo Ch. (Jurnal Rekayasa Konstruksi Mekanika Sipil, 2019)
productivity is the ratio between output and input, or the comparison between product results and the total resources used. Based on several field observations, the productivity of labor spread across the city of Kupang, especially in brick production, varies greatly. As a result of varying productivity, the results obtained are also very varied. This research was completed with a multiple regression analysis method that began with the collection of raw data through site surveys the distribution of questionnaires to respondents including the owners of brick companies and brick workers in the city of Kupang. Of the five external factors that are used to determine how they affect the productivity of brickworkers in Kupang City, the influence factor is the weather. The significant value of the effect of X3 on Y was 0.279 > 0.05 and the t value was 2.095 > t table 2.00758. Thus it can be concluded that H3 is accepted which means there is an influence of X3 on Y. While the other four factors namely the distance of raw materials to the production machine, cleanliness, wages and motivation do not affect the productivity of the brickworkers..